The Effectiveness of Liveworksheet Teaching Media in Teaching Grammar (An Experimental Research at The 10 Graders of SMK Gondang Pekalongan) - Hakim, Mohammad Arief Lukman; Permanasari, Pradnya (Journal of English Language and Education, 2025)
Technological advancements have transformed English language learning, particularly in grammar instruction. This study aims to evaluate the effectivenes of Liveworksheet as a digital teaching medium in improving grammar comprehension and to explore students’ perceptions of its use. A quasi-experimental method with a pretest-posttest design was employed, involving 34 tenth-grade students at SMK Gondang Pekalongan. Data were collected through written tests, interviews, and classroom observations, while a t-test was used to analyze students’ performance before and after the treatment. The findings show a significant improvement in students’ grammar comprehension, with the average score increasing from 32 in the pretest to 52 in the posttest. Students reported that Liveworksheet’s interactive features and instant feedback enhanced their motivation and engagement. However, challenges such as limited access to devices and unstable internet connections were also identified. In conclusion, Liveworksheet has proven effective in enhancing students’ grammar comprehension and learning motivation. It is recommended as a supplementary teaching tool, supported by teacher and student training and improved access to technological facilities.